Meeting fiscal challenges in Japan's rapidly ageing society - Jones, Randall S.. (OECD Economics Department Working Papers, 2019)
Japan's gross government debt of 226% of GDP in 2018 is the highest ever recorded in the OECD area, and places the economy at risk. The government now aims to achieve a primary surplus by FY 2025. Additional fiscal consolidation, based on a detailed plan covering specific spending cuts and tax increases, is necessary to put the government debt ratio on a downward trend in the face of rapid population ageing. This is a very difficult task and a stronger fiscal framework would help keep policy on track to achieve fiscal targets. Controlling social spending requires making better use of healthcare resources, in p art by reducing overinvestment in hospitals and increasing the use of generic drugs. Another priority is ensuring the sustainability of local government spending, in part by reducing costs through the joint provision of local public services and infrastructure across jurisdictions and the development of compact cities in the context of depopulation in many parts of Japan. Increased revenue should come primarily from hikes in the consumption tax rate, which is among the lowest in the OECD. In addition, disincentives to employment in the tax and benefit system should be removed, as sustained economic growth is crucial to ensure fiscal sustainability. This Working Paper relates to the 2019 OECD Economic Survey of Japan (http://www.oecd.org/economy/japan-economic-snapshot/)